Chemistry of 4-[(4-bromophenyl)ethynyl]pyridine at metal surfaces studied by STM. Issue 67 (2nd August 2018) - Ren, Jindong; Larkin, Eugene; Delaney, Colm; Song, Yang; Jin, Xin; Amirjalayer, Saeed; Bakker, Anne; Du, Shixuan; Gao, Hongying; Zhang, Yu-Yang; Draper, Sylvia M.; Fuchs, Harald
Abstract : The DFT optimized 44BEP on metal (M) surfaces. The change of binding energy ( E b ) and distances ( d Br_sub and d N_sub ) on different surfaces will bring different configurations and self-assembling behaviours. Abstract : Molecular architectures (Kagome networks, coordinated/covalent dimers and branched coordination chains) via self-assembly, Ullmann reaction and pyridine coordination of 4-[(4-bromophenyl)ethynyl]pyridine are found to be sensitive to the underlying metallic surfaces. The molecular species were characterised on the surface by low-temperature scanning tunnelling microscopy (LT-STM) at sub-molecular level.